Sex-wise changes in haematological and biochemical parameters before and after exchange transfusion in neonatal hyperbilirubinemia - Joshi, Ishan; Sharma, Amit (International Journal of Research in Medical Sciences, 2019)
Background: Exchange transfusion (ET) is required in hyperbilirubinemic hospitalized neonates. Methods: The study center at SMS and associated hospitals. The blood bank is licensed and fully equipped. Fall in serum bilirubin minimum of 40 cases was required as the sample size of the present study. Results: The Sex ratio in the neonates undergoing Exchange transfusion was 65% (26) Males and 35% (14) females. The mean values of Hb (g/dl), Hematocrit and Direct bilirubin (mg/dl) of male and female before and after exchange transfusion, were non-significant. Conclusion: Exchange transfusion was required more commonly in male neonates. The mean values of change in Hb (g/dl), Hematocrit and Direct bilirubin (mg/dl) of males and females before and after exchange transfusion, were non-significant. The mean values of change in Indirect bilirubin (mg/dl) in both males and females before and after exchange transfusion was highly significant. The mean values of change in Total bilirubin (mg/dl) in males and in females were significant.